QnrS1- and Aac(6′)-Ib-cr-Producing Escherichia coli among Isolates from Animals of Different Sources: Susceptibility and Genomic Characterization - Jones-Dias, Daniela; Manageiro, Vera; Graça, Rafael; Sampaio, Daniel A.; Albuquerque, Teresa; Themudo, Patrícia; Vieira, Luís; Ferreira, Eugénia; Clemente, Lurdes; Caniça, Manuela (Frontiers in Microbiology, 2016)
Salmonella enterica and Escherichia coli can inhabit humans and animals from multiple origins. These bacteria are often associated with gastroenteritis in animals, being a frequent cause of resistant zoonotic infections. In fact, bacteria from animals can be transmitted to humans through the food chain and direct contact. In this study, we aimed to assess the antibiotic susceptibility of a collection of S. enterica and E. coli recovered from animals of different sources, performing a genomic comparison of the plasmid-mediated quinolone resistance (PMQR)-producing isolates detected. Antibiotic susceptibility testing revealed a high number of non wild-type isolates for fluoroquinolones among S. enterica recovered from poultry isolates. In turn, the frequency of non-wild-type E. coli to nalidixic acid and ciprofloxacin was higher in food-producing animals than in companion or zoo animals. Globally, we detected two qnrS1 and two aac(6’)-Ib-cr in E. coli isolates recovered from animals of different origins. The genomic characterization of QnrS1-producing E. coli showed high genomic similarity (O86:H12 and ST2297), although they have been recovered from a healthy turtle dove from a Zoo Park, and from a dog showing symptoms of infection. The qnrS1 gene was encoded in a IncN plasmid, also carrying blaTEM-1-containing Tn3. Isolates harboring aac(6’)-Ib-cr were detected in two captive bottlenose dolphins, within a time span of two years. The additional antibiotic resistance genes of the two aac(6’)-Ib-cr-positive isolates (blaOXA-1, blaTEM-1, blaCTX-M-15, catB3, aac(3)-IIa and tetA) were enclosed in IncFIA plasmids that differed in a single transposase and 60 single nucleotide variants. The isolates could be assigned to the same genetic sublineage – ST131 fimH30-Rx (O25:H4), confirming clonal spread. PMQR-producing isolates were associated with symptomatic and asymptomatic hosts, which highlight the aptitude of E. coli to act as silent vehicles, allowing the accumulation of antibiotic resistance genes, mobile genetic elements and other relevant pathogenicity determinants. Continuous monitoring of health and sick animals towards the presence of PMQR should be strongly encouraged in order to restrain the clonal spread of these antibiotic resistant strains.